Complications, Additional Surgery , and Joint Survival Analysis After Medial Open-Wedge High Tibial Osteotomy - (:unkn) unknown (SLACK INC, 2020)
The reported incidence of complications following medial open-wedge hightibial osteotomy (MOWHTO) varies. The authors sought to assess the complications,additional surgeries, and joint survival following MOWHTO in patients with isolated medial compartment arthrosis during a mean follow-up of 10 years. This retrospective study involved patients implanted with spacer plates,angle adjustable plates, or inverse L-type plates with wedges between 2000 and 2010. A total of 504 knees from 441 patients were examined. Mean age of the study population was 52.6 +/- 7.0 years, with 56 (11.1%) knees from men and 448 (88.9%) from women. The 10-year Kaplan-Meier joint survival rate was 94.8%. Overall complication rate for MOWHTO was 63.7%, with complications in 20.3% of treated knees requiring additional surgery. In this population,although the overall complication rate and the need for additional surgery were high, the need for additional surgery resulting from serious complications was low (2.6%). The high joint survival rate and low rate of additional surgery for serious complications indicate that MOWHTO can be safely applied in patients with isolated medial gonarthrosis.
Keywords: UNICOMPARTMENTAL KNEE ARTHROPLASTY; LONG-TERM SURVIVAL; BIOLOGICAL AGE; CLOSING WEDGE; CLOSED WEDGE; COMPARTMENT OSTEOARTHRITIS; VARUS GONARTHROSIS; PHYSICAL-FITNESS; VALGUS OSTEOTOMY; PUDDU PLATE